Catalytic depolymerization of the dealkaline lignin over Co–Mo–S catalysts in supercritical ethanol. (February 2022) - Hao, Guojun; Liu, Hongying; Chang, Zhibing; Song, Kechen; Yang, Xin; Ma, Han; Wang, Wenjing
Abstract: In this work, lignin depolymerization was examined over CoMo sulfide catalysts supported on different carriers in supercritical ethanol system. The temperature, time, MoS2 and carrier effects on the lignin depolymerization were investigated. 95.76% liquefaction yield with negligible char was achieved over Co–Mo–S/ZrO2 at 340 °C for 150 min. The liquid product was mainly composed of C4 –C8 alcohols, C4 –C10 esters and C7 –C10 aromatic compounds. The synergistic effect of active sites and acid-base sites on support played an important role in lignin depolymerization. Furthermore, the Co–Mo–S/ZrO2 catalyst is reusable with 8% loss in liquefaction yield after 5 cyclic runs. We believe that acid/base carriers or additives that can promote the medium to generate abundant free radicals or ions to replace external hydrogen pressure are one of the prospects for the design of depolymerization lignin catalysts. Graphical abstract: Image 1 Highlights: Lignin depolymerization was presented using bifunctional CoMo sulfide catalysts. Reaction temperature showed a great effect on lignin depolymerization. The nature of the carrier affects the degree of vulcanization of Mo. The acidic and basic sites on the carrier could greatly promote the ethanol self-evolution reaction. Amphoteric carrier has more advantages in depolymerizing lignin.